E-BOOK SEBAGAI INOVASI DALAM PEMENUHAN SARANA DAN PRASARANA PENDIDIKAN BERBASIS TEKNOLOGI DI ERA DIGITAL PASCA PANDEMI COVID-19 - Raihani Afifah; Petra Kristi Mulyani (Universitas Terbuka, 2022)
This article discusses an innovation of facilities and infrastructure to support the quality of education in Indonesia. Difficulties in the distribution and outreach of facilities and infrastructure such as textbooks to schools that are far from the center of government are also an obstacle. This causes the problem of uneven distribution of education in Indonesia. For this reason, innovation is needed so that students access the information they should get easily and affordable throughout the archipelago. The purpose of writing this article is to explain the effect of using technology media, namely electronic books or ebooks for schools. This research is a literature study. This article discusses the use of electronic books or ebooks as supporting educational facilities and infrastructure after the Covid-19 pandemic.